Membangun SDM dengan Karakteristik Perilaku Kewirausahaan: Studi Pada Mahasiswa Sebuah Perguruan Tinggi Swasta di Indonesia [Building Human Resource Through Entrepreneurial Characteristics: Study of Students in a Private University in Indonesia] - Lim, Fredy; Sembel, Jacquelinda Sandra (Universitas Pelita Harapan, 2022)
This research aims to provide an analysis of the factors that may affect the behavior of or give rise to entrepreneurial characteristics. The lack of entrepreneurs in Indonesia becomes the focus and subject of this research as most of them hold a common mindset of “job seeker”, meaning that they would seek jobs upon finishing their degree. The author hopes that this research would be able to build the mindset of university students in general. This research relies upon the quantitative approach in which electronic questionnaires were used as a method to gather samples. Said sample amounted to 300 active Pelita Harapan University students. The data were then assessed in accordance with the validity and reliability analysis. The software used was SPSS, mainly to process the data gathered. Preliminary analysis to check its validity and reliability involves 30 of the participants’ data. Upon verification, all 300 data were then used to come up with the actual result. The result suggested that there are several factors that may affect the behavior of or give rise to entrepreneurial characteristics.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi perilaku karakteristik kewirausahaan mahasiswa perguruan tinggi di Indonesia. Penelitian ini didasari pada fenomena masih rendahnya jumlah wirausaha di Indonesia yang disebabkan oleh pola pikir masyarakat, terutama mahasiswa yang cenderung memilih sebagai job seeker setelah lulus dari universitas. Peneliti berharap agar penelitian ini dapat membangun SDM dengan karaketeristik kewirausahaan, terutama pada mahasiswa di perguruan tinggi di Indonesia. Penelitian ini menggunakan pendekatakan kuantitatif dengan menggunakan survei melalui elektronik kuesioner sebagai metode pengumpulan sampel. Sampel yang digunakan berjumlah 300 mahasiswa aktif di Universitas Pelita Harapan. Data diolah dengan analisis validitas dan reliabilitas dengan menggunakan software SPSS sebagai aplikasi pengolahan data. Dari hasil penelitian, dapat disimpulkan bahwa tujuh variabel berpengaruh secara siginifikan untuk membangun karakteristik perilaku kewirausahaan pada mahasiswa Universitas Pelita Harapan, yaitu: taking calculated risks, persistence, commitment, goal of definition, systematic planning, persuasion, dan independence.